2019
DOI: 10.4314/mmj.v31i2.12
|View full text |Cite
|
Sign up to set email alerts
|

An evidence-based policy brief: improving the quality of postnatal care in mothers 48 hours after childbirth

Abstract: Introduction Malawi is experiencing slow progress in postnatal care of mothers within the first 48 hours after childbirth. Malawi Demographic and Health Survey (MDHS) 2015–16 reported a slow progress in postnatal care of mothers in the first 48 hours at 42% from 41% in 2010 despite a high number of institutional births. This is a critical period as a large proportion of maternal deaths occur during this period, currently at 439 per 100,000 live births. During postnatal care the mother is given imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…31 Furthermore, although WHO Postnatal care recommendations do exist, there is a paucity of literature providing guidance and frameworks to health workers at country or system level on how to provide high quality maternal care, particularly after facility birth. 32 As a result, the care provided is often incomplete and not universal to every women at birth. 17 Although not universal, women from Eastern Uganda were noted to receive the highest coverage of immediate postnatal care after facility birth.…”
Section: Discussionmentioning
confidence: 99%
“…31 Furthermore, although WHO Postnatal care recommendations do exist, there is a paucity of literature providing guidance and frameworks to health workers at country or system level on how to provide high quality maternal care, particularly after facility birth. 32 As a result, the care provided is often incomplete and not universal to every women at birth. 17 Although not universal, women from Eastern Uganda were noted to receive the highest coverage of immediate postnatal care after facility birth.…”
Section: Discussionmentioning
confidence: 99%
“…Other barriers to PNC from our study have been previously reported and these include lack of resources [ 42 44 ], negative attitude of health care workers [ 22 , 45 ], cultural values [ 32 , 36 ] and cultural practices, restrictions, and confinement, and myths during the puerperium [ 41 ]. distance [ 23 , 24 , 32 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 91%
“…distance [ 23 , 24 , 32 , 46 , 47 ]. To overcome challenges associated with distance there is a need to incorporate PNC services into the village health clinics and outreach clinics like under-five clinics [ 42 ] because this will make them accessible to many within their communities. To realize that goal, health workers that run the community-based clinics will need to be trained for them to provide the required PNC services.…”
Section: Discussionmentioning
confidence: 99%
“…While WHO recommends remaining in the facility for postnatal care for 24 hours following facility birth, when the most deaths occur [ 12 ], women and newborns in Malawi are often discharged earlier due to availability of space and funding. Additionally, facilities do not always prioritise allocating skilled providers for care following uncomplicated births [ 13 ]. These shortages of qualified staff as well as essential equipment represent contributors to delayed and incomplete care [ 14 ].…”
Section: Introductionmentioning
confidence: 99%